TRANSPARANSI DAN AKUNTABILITAS DALAM PASAR MODAL MELALUI ANALISIS HUKUM PERDATA KEWAJIBAN PENGUNGKAPAN INFORMASI - M. Haekal Febrian; Jasman Nazar (JOURNAL OF LAW AND NATION, 2024)
Indonesia's capital market, where businesses sell bonds and stocks to the general public, is vital to the country's economy. Although investors anticipate a profit, their behavior can occasionally be irrational, particularly in the event of unfavorable news that prompts a rapid sell-off that lowers projected return. Through the values of responsibility to the law and transparency to the economy, the capital market plays a critical role in fostering investor confidence and economic progress. This study's methodology, which takes a civil law approach, focuses on the examination and interpretation of legal provisions pertaining to information disclosure requirements, legal accountability, and transparency in the stock market. This strategy is implemented through an examination of the laws that control information disclosure in the stock market. The study's findings highlight how crucial financial reporting openness is to fostering investor trust in the capital market. truthful and precise financial data.